Risk Factors for Rubella Transmission in Kuyu District, Ethiopia, 2018: A Case-Control Study - Abdulkadir, Abdulbari; Gebrehiwot, Tsegaye Tewelde (Interdisciplinary Perspectives on Infectious Diseases, 2019)
Background. Rubella is a vaccine-preventable disease associated with a significant morbidity and adverse pregnancy outcomes, mainly if acquired in the first trimester of pregnancy with serious consequences to the fetus. Despite increased episodes of rubella epidemics (127 outbreaks in 2009–2015), rubella national vaccination is not yet introduced in Ethiopia. In January 2018, an increase of fever and rash cases was reported in Kuyu District of Oromia. We investigated the outbreak to confirm rubella, determine risk factors, and guide interventions. Methods. We identified rubella cases from health centers and conducted a case-control study (1 case : 2 controls) with 150 participants, from March 12 to 15, 2018. Cases were people who presented with fever and rash or laboratory-confirmed cases. Controls were age matched (<15 yrs) with neighbors selected purposively. We interviewed parents by a structured questionnaire and observed the housing condition. Variables include sex, age, vaccination status, family size, contact history, housing condition, and travel history. Simple logistic regression was used to select the candidate variable at a P value <0.25. We identified risk factors at P<0.05 with AOR and 95% CI by multivariate logistic regression. Results. We identified 50 cases (with no death), and out of them, seven (14%) were confirmed cases (rubella IgM positive). The mean age of the cases was 6 ± 3 years and of the controls was 8 ± 4 years. Family size >5 (AOR = 2.4; 95% CI: 1.5–4.11), not well-ventilated living room (AOR = 4.7; 95% CI: 3.43–8.12), history of contact with rash people (AOR = 2.2; 95% CI: 1.6 3.5), no history of diarrhea in the last 14 days (AOR = 0.8; 95% CI: 0.6–0.9), and no history of vitamin A supplementation (AOR = 2.9; 95% CI: 1.7–2.6) were significant factors for rubella infection. Conclusions. We identified rubella outbreak in the rural area. Crowded living condition, large family size, not receiving vitamin A in the last 6 months, and contact with people with symptoms of rubella were factors that drove the outbreak, while not having diarrhea in the last 14 days was the protective factor. We recommended the introduction of rubella immunization national programs and advocated the policy on rubella vaccine and strengthening surveillance for congenital rubella syndrome and rubella.